Integration of Planning, Organizing, Implementation, and Evaluation in Improving the Effectiveness of In-Depth Learning Management in Elementary Schools - Lisa Virdinarti Putra; Sisca Septiani; Nur Intan Rochmawati; Wiwik Pudjaningsih; Siswi Yulfani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Creative thinking is a key 21st-century skill, yet its development in elementary education remains limited due to traditional, teacher-centered methods. While inquiry-based learning promotes cognitive engagement and gamification fosters motivation, few instructional models combine both to enhance creativity systematically. This study developed and validated the INGAME model (Inquiry Model with Gamification Elements) using the ADDIE instructional design framework. A research and development (RD) approach guided the model’s creation, expert validation, and classroom implementation. Participants included 23 fifth-grade students and one teacher from an Indonesian public elementary school. Data were gathered through expert validation sheets, teacher and student questionnaires, creative thinking rubrics, observations, and interviews, then analyzed using descriptive statistics and thematic analysis. Validation results showed high content and structural validity (mean = 90.16%). Practicality, based on teacher feedback, was rated as high (mean = 82%). Effectiveness was confirmed through both student self-assessments (mean = 79%) and creative thinking rubric scores, which showed improvement across Torrance’s four indicators: fluency, flexibility, originality, and elaboration (average gain = +1.13). Observation data revealed active student engagement throughout the model’s eight gamified inquiry phases, averaging 85.8% participation. The INGAME model successfully integrates cognitive rigor with motivational design, offering a structured, scalable solution for fostering creativity in elementary classrooms. It contributes to educational innovation aligned with SDG 4 and national curriculum reform by operationalizing “motivated constructivism” through inquiry and gamification.